INTEGRATING RELIGIOUS HABITUATION AND LIFE SKILLS TO STRENGTHEN GRADUATE COMPETENCIES IN ISLAMIC SCHOOLS - Ali Masyharudin (Journal Of Islamic Education And Pesantren, 2021)
This study aims to analyze the integrative model of religious habituation and life skills in strengthening the Graduate Competency Standards (GCS) at SMA Islam Sunan Ampel Seblak Jombang. The research employed a qualitative case study approach conducted in a natural school setting. Data were collected through observation, in-depth interviews, and documentation, and analyzed interactively through data reduction, data display, and verification using triangulation techniques. The findings reveal that the strengthening of GCS is achieved through a systemic integration of religious habituation and vocational skill development programs. Religious practices such as congregational prayers, Qur’anic recitation, and other spiritual activities foster discipline, responsibility, and spiritual awareness among students. Meanwhile, life skill programs including vocational training and entrepreneurship enhance personal, social, and vocational competencies. This integration contributes to the balanced development of attitudes, knowledge, and skills as outlined in the GCS. The model demonstrates that Islamic education integrating religious values and life skills can produce graduates who are religious, independent, adaptive, and competitive.